Truth and procedural fairness in Chinese criminal procedure law - Alexander Shytov (2019)
© The Author(s) 2019. Chinese criminal procedural law has recently been undergoing rapid transformation. While the search for ‘truth’, embodied in a confession by the accused, has traditionally dominated the criminal process, efforts are now being made to secure more procedural fairness. This is exemplified by the introduction of rules to render inadmissible at trial confessions extorted from suspects by ill treatment. Unsurprisingly, it has proved difficult to shift the mindsets of the players in the criminal justice process. The new rules have not been fully implemented in many respects and there is still confusion over the criteria to be used by the courts in making decisions about inadmissibility. Further, it has proved difficult to enable defence lawyers to play a more active role in defending their clients and to render it normal for witnesses to testify at trial. This handicaps the drive to secure a better balance between the search for truth and procedural fairness in the Chinese criminal trial.